Discrete element modelling of the packing of spheres and its application to the structure of porous metals made by infiltration of packed beds of NaCl beads - Langston, P.; Kennedy, Andrew R. (Elsevier, 2014)
A numerical model, using the discrete element method, has been developed to quantify specific parameters that are pertinent to the packing behaviour of relatively large, spherical NaCl beads and mixtures of beads of different sizes. These parameters have been compared with porosity and connectivity measurements made on porous aluminium castings made by molten metal infiltration into packed beds of such beads, after removal of the NaCl by dissolution. DEM has been found to accurately predict the packing fraction for salt beads with both mono and binary size distributions and from this the pore fractions in castings made by infiltration into packed beds of beads could be predicted. Through simple development of the condition for contacting of neighbouring beads, the number of windows linking neighbouring pores, and their size, could also be predicted across a wide range of small bead additions. The model also enables an insight into the mixing quality and changes in connectivity introduced through the addition of small beads. This work presents significant progress towards the delivery of a simulation based approach to designing preform architectures in order to tailor the resulting porous structures to best suit specific applications.